Reproductive hormones and sex chromosomes drive sex differences in the sleep–wake cycle - Ralston, Micah; Ehlen, J. Christopher; Paul, Ketema (Frontiers in Neuroscience, 2024)
There are well-documented gender differences in the risk and severity of sleep disorders and associated comorbidities. While fundamental sex differences in sleep regulatory mechanisms may contribute to gender disparities, biological responses to sleep loss and stress may underlie many of the risks for sleep disorders in women and men. Some of these sex differences appear to be dependent on sex chromosome complement (XX or XY) and the organizational effects of reproductive hormones. Reproductive development plays a critical role in the ability of sex chromosomes and reproductive hormones to produce sex differences in sleep and wakefulness. Rodent models reveal that reproductive hormones drive many but not all sex differences in sleep–wake architecture. The ability of reproductive hormones to alter sleep are often dependent on responses to sleep loss and stress. However, in the absence of reproductive hormones (in gonadectomized rodents) sex differences in sleep amount and the ability to recover from sleep loss persist. The suprachiasmatic nucleus (SCN) and the ventrolateral preoptic nucleus (VLPO) of the hypothalamus play crucial regulatory roles in mediating the effects of reproductive hormones on the sleep–wake cycle. Taken together, the work reviewed here reveals that the reproductive hormone environment and sex chromosome complement may underlie gender disparities in sleep patterns and the risk for sleep disorders.